From public administration to public management, from governance to govermentality: conceptual challenges to public administration - Ocampo, Romeo B. (2008)
The original symposium question is rephrased in this article to start with the general one: "Is there(still) a public administration?" with "... in the philippines?" as a concluding subtext . "yes" is the answer to both. but as a field of study and practice, public administration(PA) has undergone a number of identity crises and conceptual challenges from within and without. This article briefly describes and discuss the gauntlet presented by such key concepts as public management and public policy, governance,e - governance, and governmentality (the neologism coined by the French social historian and philosopher, Michel Foucault).PA has been buffeted by reforms and movements to broaden its concerns, to emulate private management, to adopt new technology, and to recognize a disaggregated and decentered(yet globalized) world in which the state and government are just two of the important actors. - Reproduced.
Keywords: E governance - Philippines; Management - Philippines; Public administration - Philippines; Public administration